CrAssphage and its bacterial host in cat feces - Li, Yanpeng (Sci Rep, 2021)
CrAssphages are a diverse group of related phages detected in human feces where they are the most prevalent and abundant prokaryotic virus. CrAssphages’ cellular host has been identified as the anaerobic Bacteroides intestinalis. CrAssphage has also been reported in non-human primates and environmental samples and has been proposed as a marker of human fecal contamination. Here we describe crAssphage DNA in a feline fecal sample. 95% of the ~ 100 Kb genome could be assembled and classified in genus 1 of the recently proposed Alphacrassvirinae subfamily. The cat origin of the fecal sample was confirmed by partial mitochondrial DNA sequencing. High levels of Bacteroides intestinalis DNA could also be detected in this cat’s feces. Fecal samples longitudinally collected over a 4-week period showed the continuous shedding of crAssphage DNA. We therefore report the first genome sequence-confirmed detection of crAssphage in fecal samples of a non-primate mammal.